POPULATION TREND, LANDSCAPE AND LAND DEGRADATION IN THE SELE PLAIN: A GEO-ECONOMIC FRAMEWORK - Giuseppe Forino; Luca Salvati; Luigi Perini (Bollettino della Società Geografica Italiana)
Land degradation is related to physical and biological variables and to anthropogenic factors acting as drivers of soil and landscape deterioration. The paper presents a preliminary analysis of long-term trends in selected socioeconomic variables that may have contributed to reduce soil quality in Destra Sele area (Salerno), one of the Italian regions that best represents the fragmentation of the complex mosaic of land-uses, from rural to industrial, from tourism to residential uses.